THE BIBLIOTHERAPY METHOD IN GROUP COUNSELING - Bakhrudin All Habsy; Akhsauma Dalla Arsyada; Nadia Kun Ilmawati; Shela Nurussani; Kamila Haikal Abdullah (PT Altin Riset Publishing, 2026)
Bibliotherapy is a technique used in group guidance services as an alternative to overcoming individual developmental problems in social life. This technique involves three stages, namely identification, catharsis, and insight. By reading books, learners can gain cognitive, affective, and psychomotor benefits. Group guidance services with bibliotherapy methods can also increase learners' engagement and make them more active in the learning process. This research explores the effectiveness of bibliotherapy in the context of group guidance. Using selected books, learners are given the opportunity to reflect, identify feelings, and gain new insights. The results show that bibliotherapy can increase self-understanding, reduce stress, and strengthen social skills. Therefore, group guidance services using this approach can be a valuable alternative in helping learners overcome life's challenges.